2009
DOI: 10.1073/pnas.0807774106
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing breathing motion of internal cavities in concert with ligand migration in myoglobin

Abstract: Proteins harbor a number of cavities of relatively small volume. Although these packing defects are associated with the thermodynamic instability of the proteins, the cavities also play specific roles in controlling protein functions, e.g., ligand migration and binding. This issue has been extensively studied in a well-known protein, myoglobin (Mb). Mb reversibly binds gas ligands at the heme site buried in the protein matrix and possesses several internal cavities in which ligand molecules can reside. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
109
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 36 publications
13
109
1
Order By: Relevance
“…In 12/15 lipoxygenase, a preferred route for oxygen travel has been identified that links the solvent and buried active site (6). Similarly, crystallographic and computational studies have also implicated oxygen access paths in cyclooxygenase, copper amine oxidase, cholesterol oxidase, and cytochrome c oxidase (8,10,11). The nuanced role of the protein matrix in influencing catalysis is not restricted to oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In 12/15 lipoxygenase, a preferred route for oxygen travel has been identified that links the solvent and buried active site (6). Similarly, crystallographic and computational studies have also implicated oxygen access paths in cyclooxygenase, copper amine oxidase, cholesterol oxidase, and cytochrome c oxidase (8,10,11). The nuanced role of the protein matrix in influencing catalysis is not restricted to oxygen delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these pathways are coincident with apolar cavities, which have been identified as xenon docking sites (16, 17, 28 -30). However, as also pointed out by Elber (11), there is little or no direct experimental evidence in support of multiple pathways (31,32). In the cases of mammalian myoglobins, human hemoglobin, and HbI from Scapharca inaequivalvis, almost all of the experimental evidence suggests that Ն75% of ligands enter and exit the distal pocket through a transient channel between the heme propionates, which is produced by outward rotation of the distal histidine (His(E7)).…”
mentioning
confidence: 97%
“…Yamato (27) calculated strain tensor fields induced by high pressure in lysozyme and myglobin. Recently, Yamato and coworkers have applied a similar, molecular dynamics-based approach to supplement their analyses of protein dynamics (13,28).…”
Section: Significancementioning
confidence: 99%
“…12), timeresolved crystallography (e.g., ref. 13), FRET (e.g., ref. 14), and direct pulling measurements (15,16) have been published.…”
mentioning
confidence: 99%